Evaluation of encapsulated anethole and carvone in lambs artificially- and naturally-infected with Haemonchus contortus - Katiki, L. M.; Araujo, R. C.; Ziegelmeyer, L.; Gomes, A. C.P.; Gutmanis, G.; Rodrigues, L.; Bueno, M. S.; Veríssimo, C. J.; Louvandini, H.; Ferreira, J. F.S.; Amarante, A. F.T. [UNESP] (Elsevier, 2019)
Molecules from natural sources, such as essential oils, have shown activity against parasites in vitro, but have not yet been explored extensively in vivo. Anethole and carvone (10% each), encapsulated with 80% of a solid matrix, referred to as EO (encapsulated oils), were tested in vivo in 2 experiments. In Experiment 1: Lambs were artificially infected with multidrug resistant Haemonchus contortus, or left uninfected, and treated (or not) with 50 mg/kg bw (body weight) of EO in a controlled environment. Thirty-two male lambs were kept in individual cages for a period of 45 days, after which animals were evaluated for parasitological, hematological, toxicological, and nutritional parameters. After 45 days of treatment, EO at 50 mg/kg bw provided a significant (P ≤ 0.05) reduction in fecal egg count (FEC). Although FEC was reduced, animals from both treatments had similar counts of total adult worms. The low FEC was caused probably by a significant reduction (P ≤ 0.05) in both male worm size and female fecundity. Dry matter intake of uninfected controls was significantly (P ≤ 0.05) reduced, although no toxicity was observed in treated animals. Thus, in Experiment 2, conducted for five months we used an EO dose of 20 mg/kg bw. Thirty-four weaned lambs, free of parasites, were divided in two groups and kept in collective pens. One group received EO at 20 mg/kg bw mixed with concentrate for 5 months and the other was kept as a control group (CTL). Parasitological and hematological parameters as well as body weight were evaluated. In the first 2.5 months, CTL and EO groups were confined, and both presented similar clinical parameters. Then, animals were allotted to graze on contaminated pastures to acquire natural infection for the next 2.5 months. The infection was patent after 25 days and both groups had similar decreases in weight gain, increases in FEC, and decreases in blood parameters. Coprocultures from CTL and EO groups established that parasite population was 90% Haemonchus sp. We concluded that the technology of encapsulation is safe and practical to deliver to lambs at the farm level and anethole and carvone at 50 mg/kg bw caused a significant decrease in FEC and, consequently, in pasture contamination by free living stages of H. contortus. However, EO at 20 mg/kg bw was not effective to prevent or treat sheep naturally-infected with gastrointestinal nematodes.
Keywords: Anethole; Carvone; Encapsulation; Essential oil; Haemonchus